Determinants of accessibility to primary sexual reproductive health care among vulnerable women in Canada: a scoping review protocol. Issue 9 (3rd September 2020) - Jarvis, Kimberly; Farrell, Alison; Richter, Solina; Lukewich, Julia
ABSTRACT: Objective: The objective of the review is to describe, synthesize and document the determinants that impact a vulnerable woman's access to primary sexual reproductive health care in Canada. Introduction: Canada is committed to advancing sexual reproductive health care initiatives. Although both men and women require sexual reproductive health care, the implications for women are far more significant. While Canadian women do generally experience "good health, " issues with sexual reproductive health do exist, particularly for vulnerable women for whom questions about accessibility arise. Therefore, there is a need to understand the true extent of a woman's access to sexual reproductive health in Canada. Findings will be used to inform future implementation research and provide recommendations to key stakeholders. Inclusion criteria: Studies on primary access to sexual reproductive health care for vulnerable women (those living in poverty, with risky sexual behaviors, and/or are Indigenous, immigrants or refugees) aged nine to 49 who reside in Canada will be considered. Studies published in French or English from 2008 will be included. Women with a physical and/or mental disability and/or who are part of the lesbian, gay, bisexual, transgender and queer community will be excluded if they do not have one or more of the defining characteristics listed above. Methods: Databases to be searched include PubMed, Embase, CINAHL, PsycINFO, Sociological Abstracts and Women's Studies International. Gray literature searches will also be conducted. Following screening, all identified citations will be collated. Titles and abstracts will be screened by independent reviewers. Potentially relevant studies will be retrieved in full and assessed. Data will be extracted by independent reviewers and presented in diagrammatic or tabular form and accompanied by a narrative summary.